Papers of Sir William Henry Beveridge, 1st Baron Beveridge (as filmed by the AJCP) [M2616-2618] - Beveridge, William Henry Beveridge, Baron, 1879-1963.; Australian Joint Copying Project; National Library of Australia; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1950)
Selections from the Beveridge papers relating to Australia and New Zealand. Contains: 1. General and personal letters, 1921-1962. 2. Other interests and activities: crusade for world government, 1948. 3. visits abroad: New Zealand and Australia, 1948.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project miscellaneous series M2616-2618.
Also available online
Microfilm copy of originals held by British Library of Political and Economic Science, London School of Economics and Political Science, London.
Director, London School of Economics, 1919-37; Master of University College, Oxford, 1937-44; Liberal M.P., 1944-1945 and author.
Keywords: Beveridge, William Henry Beveridge, -- Baron, -- 1879-1963 -- Archives; Economists -- Great Britain -- Archives; International organization; New Zealand -- Description and travel; Australia -- Description and travel -- 1901-1950.